The rights of indigenous peoples and the establishment of marine protected areas in the traditional inuit territory - Tugend, Mana, 1994- (2019)
Verkefnið er lokað til 24.09.2090. States have the duty to protect the environment, including but not limited to the ocean. At the same time, states have the duty to respect, protect and fulfill the rights of indigenous peoples. While climate change urges action to protect the environment, it shall include the relevant stake- and rights holders, such as indigenous peoples. Hence, this thesis analyzes the relationship between indigenous peoples and marine protected areas (MPAs). It addresses the question to know whether the rights of indigenous peoples are being fulfilled when it comes to the establishment, management and control of MPAs. To this end, three case studies relating to the establishment of MPAs in the territory of the Inuit people are being analyzed, namely the Tallurutiup Imanga National Marine Conservation Area in Lancaster Sound, Nunavut; the Imappivut Marine Plan off the coast of Labrador, Nunatsiavut; and the Management Plan in the Pikialasorsuaq polynya which is shared between Canada and Greenland. The thesis analyzes the potential attached to the creation of these MPAs both for the protection of the environment and for the fulfillment of the rights of the Inuit people. It goes further by analyzing the possibilities to create a network of MPAs through these MPAs. However, while the establishment of these MPAs sounds promising in theory and show a clear evolution with respect to conservation methods excluding indigenous peoples, only the future will tell how efficient these are in practice.